2001
DOI: 10.1128/jb.183.19.5772-5777.2001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Recombination in Bacillus subtilis 168: Effect of Δ helD on DNA Repair and Homologous Recombination

Abstract: The B. subtilis ⌬helD allele rendered cells proficient in transformational recombination and moderately sensitive to methyl methanesulfonate when present in an otherwise Rec ؉ strain. The ⌬helD allele was introduced into rec-deficient strains representative of the ␣ (recF strain), ␤ (addA addB), ␥ (recH), (⌬recU), and (⌬recS) epistatic groups. The ⌬helD mutation increased the sensitivity to DNA-damaging agents of addAB, ⌬recU, and ⌬recS cells, did not affect the survival of recH cells, and decreased the sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…HelD is a helicase implicated in DNA repair and homologous recombination (13). In addition, the interaction of this protein with the RNA polymerase has a stimulatory effect on transcription cycling and elongation (14).…”
Section: Resultsmentioning
confidence: 99%
“…HelD is a helicase implicated in DNA repair and homologous recombination (13). In addition, the interaction of this protein with the RNA polymerase has a stimulatory effect on transcription cycling and elongation (14).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, SsbA/SSB must be displaced from the ssDNA to assemble the RecA presynaptic filament. ), suggesting that RecA recruitment and/or RecA filament modulation by RecF, RecO and RecR might occur in a concerted manner (single step) Wang et al, 1993;Carrasco et al, 2001). Genetic studies have demonstrated that a recF, recO or recR defect is partially overcome by common suppressors in both B. subtilis and E. coli, (e.g.…”
Section: Recombinase Loadingmentioning
confidence: 99%
“…B. subtilis contains two proteins showing homology to UvrD, namely, PcrA and YjcD (53,307). PcrA is an essential helicase in B. subtilis, and the pcrA gene is able to complement the UV sensitivity conferred on E. coli lacking uvrD (307).…”
Section: Recd2 Is a Possible Mismatch Repair Helicase In Bacillusmentioning
confidence: 99%